PEMBERIAN VCO (VIRGIN COCONUT OIL) PADA Tn. M DENGAN DIAGNOSIS MEDIS CVA INFARK DENGAN MASALAH KEPERAWATAN RISIKO KERUSAKAN INTEGRITAS KULIT DI RUANG ICU CENTRAL RUMKITAL dr. RAMELAN SURABAYA - Eppy Setiyowati (Jurnal Ilmu Kesehatan dan Kesehatan, 2017)
Abstract: Ulcus decubitus is a serious dermal (skin) problem, especially for the unconscious patients with the lack of mobilization hospitalized in the ICU. It appears in the area which is localizedwith the necrotic tissues; it also usually appears on the surface of protruding bones, resulted fromthe long term pressure which increases the capillary pressure. This study was purposed to analyzethe effectiveness of the use of VCO to the patient with the risk of having ulcus decubitus in thecentral ICU of Rumkital Dr. Ramelan Surabaya (Surabaya Navy Hospital). The design used in thisstudy was case study done by investigating a problem through one case comprising of a single unit.The variable used in this study was the use of VCO to the patient with the risk of ulcus decubitus.The data were analyzed descriptively done by using inductive approach. The result of this studyconcludes that the use of VCO to Mr. M who has the risk of impaired skin integrity is effective toprevent decubitus.